(untitled) (Bangladesh Journal of Microbiology, 2010)
Petroleum ether, chloroform, ethyl acetate and ethanol extracts of Calycopteris floribunda leaves were investigated for their antimicrobial activities against ten human pathogenic bacteria and five phytopathogenic fungi using disc diffusion and poisoned food method respectively. The extracts showed good antibacterial and antifungal activity against the organisms tested herein. The chloroform extract exhibited the largest zone of inhibition (35 mm in diameter with 2 mg/disc extract) against Pseudomonas aeruginosa, and the highest inhibition of fungal radial mycelial growth (71.5% with 100 mg extract/ml medium) was recorded against Alternaria alternata using the same extract. The minimum inhibitory concentration (MIC) values were determined by broth macrodilution method and the lowest was recorded against P. aeruginosa (MIC 250 μg/ml) among the bacterial isolates and A. alternata (125 μg/ml) among the fungal isolates. The crude chloroform extract was found to be active against most of the fungal pathogens. So it may be used as a novel antimicrobial agent for controlling a number of pathogens. Keywords: Antimicrobial activity; Calycopteris floribunda; leaf extract DOI: http://dx.doi.org/10.3329/bjm.v25i2.4877 Bangladesh J Microbiol, Volume 25, Number 2, December 2008, pp 137-139